2015
DOI: 10.1177/2229411220150305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cervical Preflaring on Initial Apical File Size Determination in Maxillary Central Incisors and First Molars

Abstract: Background: Cervical or coronal preflaring allows a more accurate assessment of the apical diameter of the root canal. This article investigates the influence of cervical preflaring-using different rotary instruments on the determination of initial apical width of the canal. Materials and Methods: 40 maxillary central incisors and maxillary first molars were assigned for this study. Actual canal length (working length [WL]) was determined with patency file. The teeth were divided into four Sub groups-Sub Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have mentioned that it is beneficial to eliminate coronal third obstruction before doing apical instrumentation. Multiple studies have suggested that modifying the upper third of the canals affects the dimensions of the file that fits tightly at the tip [ 14 , 15 ]. Advancements in this domain have led to the creation of novel types of rotary tools that are specifically engineered for cervical flaring.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mentioned that it is beneficial to eliminate coronal third obstruction before doing apical instrumentation. Multiple studies have suggested that modifying the upper third of the canals affects the dimensions of the file that fits tightly at the tip [ 14 , 15 ]. Advancements in this domain have led to the creation of novel types of rotary tools that are specifically engineered for cervical flaring.…”
Section: Introductionmentioning
confidence: 99%